1999
DOI: 10.1115/1.2893980
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Estimation of End Corrections in Extended-Duct and Perforated-Duct Mufflers

Abstract: One-dimensional models for extended-duct and perforated-duct mufflers require the introduction of end corrections in order to account for multidimensional effects at the junctions. In this paper, a numerical two-dimensional finite element calculation has been used in order to obtain information on these end corrections. The results have been validated through comparison with experimental measurements performed with a modified version of the impulse method. Then, the influence of the different geometric charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Reactive and dissipative silencers with a simple expansion chamber have been extensively investigated [1][2][3][4][5][6][7][8][9][10]. For reactive silencers, Selamet and Ji [1] studied the effect of adding inlet/outlet extensions on the suppression of the pass-bands of the dome-like transmission loss (TL) pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive and dissipative silencers with a simple expansion chamber have been extensively investigated [1][2][3][4][5][6][7][8][9][10]. For reactive silencers, Selamet and Ji [1] studied the effect of adding inlet/outlet extensions on the suppression of the pass-bands of the dome-like transmission loss (TL) pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Munjal and Gowri [7] implicitly did not consider the effect of wall thickness in their 3-D FE model inasmuch as they made use [5] did not mention the value of wall thickness but, as the end corrections are measured experimentally, they tally with the new end corrections observed in the present investigation except for D/d = 4. Generally, wall thickness varies from 1 mm to 2 mm.…”
Section: Parametric Studies For End Correctionmentioning
confidence: 91%
“…Incidentally, Torregrosa concluded experimentally that the effect of length is negligible [5]. Kang and Ji concluded that the acoustic length correction decreases with an increase in the duct extension, and the difference in the acoustic length corrections gets smaller with increase of the ratio La d , and almost independent of the chamber length for long chambers [6].…”
Section: Parametric Studies For End Correctionmentioning
confidence: 99%
See 2 more Smart Citations